Cluster effect of additives in precursors for inorganic perovskites solar cells. (20th January 2020) - Wu, Yanhua; Wang, Yudi; Duan, Jialong; Yang, Xiya; Zhang, Jihua; Liu, Liming; Tang, Qunwei
Abstract: The interaction between solvent molecules and lead halides in precursor solution is important in controlling perovskite film morphology and crystallization process, which determines the photovoltaic performances of solar cells. Herein, we demonstrate two organic solvent molecules, acetonitrile (ACN) and N -methyl-2-pyrrolidone (NMP) with adverse coordinating capacity to Pb 2+ center, as precursor additives to control the interaction between dimethyl formamide (DMF) and PbBr2 and therefore the crystallization process of CsPbBr3 films. By carefully varying the concentration of additives (ACN and NMP) in DMF solutions, the final perovskite films with markedly enlarged grains are obtained in both scenarios owing to the tuned bonding strength of PbBr2 -DMF complexes and grain growth dynamics. Upon assembling into all-inorganic CsPbBr3 perovskite solar cells, the optimized power conversion efficiencies of 9.22% and 9.53% are obtained for ACN- and NMP-containing devices, which are much higher than that of control device with average 7.38%-efficiency. More importantly, the optimal device free of encapsulation exhibits excellent stability under persistent attack at 40 °C and 90% relative humidity over 30 days. The improved perovskite film quality and device performances may pave the way for full-bromine perovskite solar cells in the future. Graphical abstract: Image 1 Highlights: Small molecular ACN and NMP are introduced into the PbBr2 precursors. The interactions between PbBr2 and DMF are regulated by ACN and NMP. The all-inorganic CsPbBr3 perovskite film presents large grain size. The charge recombination is minimized for high-performance inorganic PSCs.